Electrochemical degradation of ibuprofen and naproxen using electro-Fenton process monitored by fluorescence and chemometric methods - Gabriel, Wesley Lira (2018)
The use of fluorescence spectra and chemometric methods to monitor the electrochemical degradation of the drugs ibuprofen (IBU) and naproxen (NAP) using electro-Fenton process with boron-doped diamond (BDD) is the aim of this work. The variables of the degradation process were studied and optimized using design of experiments. Percentage of chemical oxygen demand removal was used as response in the design of the experiments. The results of the central composite design showed that the best conditions to perform the degradation were 60 mA cm -2 of current density, 5500 mg L -1 of Na 2 SO 4 as support electrolyte and 30 mg L -1 of Fe 2+ as catalyst. Solutions of 30 mg L -1 of the drugs were degraded, and aliquots were taken during 1h. TOC removal, fluorescence spectra, and HPLC were used to evaluate the degradation solutions of IBU, NAP and the mixture of the compounds (MIX). The fluorescence spectra were treated with chemometric methods, i.e., parallel factors analysis (PARAFAC), multivariate curve resolution with alternating least squares (MCR-ALS) and partial least squares regression (PLSR). Models were built for each method and compared. The best fit was obtained with MCR-ALS method using fixed excitation wavelength (242 nm), and emission spectra scanned from 260 to 410 nm. The MCR-ALS was capable of recovering the pure emission spectra of the drugs and some byproducts generated. Also, the concentrations profiles of each compound were obtained. The fluorescence spectra of the compounds decreased significantly in less than 1 hour, which suggests a possible reduction of the toxicity of the solution. Results of separation and quantification obtained by HPLC with fluorescence detection were compared to the results obtained with MCR-ALS and fluorescence. Correlations high than 0.99 were achieved demonstrating that fluorescence spectroscopy associated with MCR-ALS method can substitute HPLC-fluorescence analysis in this application. Percentages of TOC removal were 77%, 65% and 63% to IBU, NAP, and MIX solution, respectively. The degradation process studied was efficient, and the monitoring method employing fluorescence and MCR-ALS showed to be fast, adequate and reliable.